Potvrđujuća pristrasnost u sprovođenju zakona i kako intervencije za uklanjanje pristrasnosti i strategije ublažavanja mogu pomoći u ponovnoj izgradnji poverenja javnosti: Tematski pregled - Segovia, Richard (NBP. Nauka, bezbednost, policija, 2024)
Purpose: This thematic review examines how confirmation bias impacts decision-making and investigative outcomes in law enforcement, aiming to identify strategies to mitigate these effects. By synthesizing existing research, this work highlights the challenges of confirmation bias and proposes practical interventions to improve fairness and accuracy in policing. Methods: Text and abstract searches were conducted using Google Scholar, Hein Law Journal Library, and the Ehrhorn Law Library. The focus was on studies examining decision-making, investigative outcomes, and methods to mitigate biases in law enforcement practices. This review followed established thematic review methodologies. Results: The literature search produced a variety of qualitative and quantitative studies. The impact of confirmation bias on decision-making, its effects on investigative outcomes, effective mitigation strategies, the role of organizational culture, and its influence on community relations were themes identified after analysis. Conclusions: This review shows the need for thorough research to validate the effectiveness of strategies designed to mitigate confirmation biases in law enforcement. Future studies should include a longitudinal focus on the impact of debiasing techniques, training programs, and organizational changes. Application in Law Enforcement: For law enforcement agencies, implementing targeted training programs, debiasing techniques, and decision-making models might improve equity and fairness concerning law enforcement practices. Addressing confirmation bias enhances investigative outcomes, builds community trust, and reinforces fairness when applying the law. Law enforcement agencies should consider adopting the strategies discussed in this review to promote more effective and ethical policing practices.